2019
DOI: 10.3390/nano9040534
|View full text |Cite
|
Sign up to set email alerts
|

Control of Membrane Fouling in Organics Filtration Using Ce-Doped Zirconia and Visible Light

Abstract: Membrane fouling has been a major issue in the development of more efficient water treatment processes. Specifically in surface waters filtration, organic matter, such as humic-like substances, can cause irreversible fouling. Therefore, this study evaluates the activity of a photocatalytic layer composed of Ce-doped zirconia nanoparticles in improving the fouling resistance during filtration of an aqueous solution of humic acid (HA). These nanoparticles were prepared by hydrothermal and sol–gel processes and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 80 publications
3
14
0
Order By: Relevance
“…This catalyst was tested as a suspended powder or immobilized on a support. In the first case, Ce-ZrO 2 nanopowder was synthesized by a sol-gel route developed in previous work [25]. In brief, for the synthesis processes, 5 mL of zirconium propoxide Zr(OC 3 H 7 ) 4 (CAS 23519-77-9, 70 wt %, Sigma-Aldrich, St. Louis, MO, United States) were mixed with 5 mL of 2-propanol (CAS 67-63-0, 99.5%, Sigma-Aldrich, St. Louis, MO, United States).…”
Section: Synthesis and Characterization Of The Ce-zro 2 Photocatalystmentioning
confidence: 99%
See 2 more Smart Citations
“…This catalyst was tested as a suspended powder or immobilized on a support. In the first case, Ce-ZrO 2 nanopowder was synthesized by a sol-gel route developed in previous work [25]. In brief, for the synthesis processes, 5 mL of zirconium propoxide Zr(OC 3 H 7 ) 4 (CAS 23519-77-9, 70 wt %, Sigma-Aldrich, St. Louis, MO, United States) were mixed with 5 mL of 2-propanol (CAS 67-63-0, 99.5%, Sigma-Aldrich, St. Louis, MO, United States).…”
Section: Synthesis and Characterization Of The Ce-zro 2 Photocatalystmentioning
confidence: 99%
“…In previous works [22][23][24][25][26], the development and testing of Ce-ZrO 2 nanoparticles was studied. An extensive characterization of the material was performed, including XRD, SEM, TEM, N 2 adsorption/desorption, diffusive reflectance, and photo-electronic characterization.…”
Section: Suspended Ce-zro 2 Nanopowdermentioning
confidence: 99%
See 1 more Smart Citation
“…The utility of surfaces with selective wettability can be further extended by incorporating them with photocatalytic nanoparticles that can degrade organic substances upon light irradiation [23][24][25]. Such a photocatalytic surface with selective wettability has demonstrated the potential for a wide range of practical applications, including anti-fouling [26,27], self-cleaning [28,29], and bactericidal coating [30]. Recent studies [31][32][33][34] have revealed that membranes with selective wettability can further benefit by incorporating photocatalytic nanoparticles that can radically transform physical filtration into chemically reactive processes.…”
Section: Introductionmentioning
confidence: 99%
“…Luster et al [36] fabricated an N-doped, TiO 2 -coated alumina membrane and demonstrated the photocatalytic degradation of carbamazepine (CBZ) as a model pollutant under simulated solar irradiation. Further, Coelho et al [26] coated a filter paper with zirconia-doped cerium to prepare a photocatalytic membrane. The membrane demonstrated flux recovery by photocatalytic degradation of humic acid as a foulant.…”
Section: Introductionmentioning
confidence: 99%